Noise exposure and children's blood pressure and heart rate: the RANCH project. Issue 9 (25th May 2006) - van Kempen, E; Van Kamp, I; Fischer, P; Davies, H; Houthuijs, D; Stellato, R; Clark, C; Stansfeld, S
Abstract : Background: Conclusions that can be drawn from earlier studies on noise and children's blood pressure are limited due to inconsistent results, methodological problems, and the focus on school noise exposure. Objectives: To investigate the effects of aircraft and road traffic noise exposure on children's blood pressure and heart rate. Methods: Participants were 1283 children (age 9–11 years) attending 62 primary schools around two European airports. Data were pooled and analysed using multilevel modelling. Adjustments were made for a range of socioeconomic and lifestyle factors. Results: After pooling the data, aircraft noise exposure at school was related to a statistically non-significant increase in blood pressure and heart rate. Aircraft noise exposure at home was related to a statistically significant increase in blood pressure. Aircraft noise exposure during the night at home was positively and significantly associated with blood pressure. The findings differed between the Dutch and British samples. Negative associations were found between road traffic noise exposure and blood pressure, which cannot be explained. Conclusion: On the basis of this study and previous scientific literature, no unequivocal conclusions can be drawn about the relationship between community noise and children's blood pressure.